1997
DOI: 10.1002/(sici)1097-0142(19970615)79:12<2336::aid-cncr7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of resistance-related proteins (metallothioneins, glutathione-S-transferase ?, heat shock protein 27, and lung resistance-related protein) in osteosarcoma

Abstract: BACKGROUND The prognosis for patients with osteosarcoma has improved over the past 20 years, mainly due to developments in chemotherapy. Some proteins have been reported to show drug resistance. Theoretically, overexpression of some of these proteins makes treatment difficult, leading to poorer outcome. METHODS Specimens taken from conventional osteosarcomas of the extremity bones from 60 patients younger than 30 years were used. In all cases, preoperative oncostatic chemotherapy was undertaken after biopsy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 35 publications
(41 reference statements)
4
65
0
Order By: Relevance
“…The prognostic value of Pgp in patients with osteosarcoma also should be examined in the context of other proposed molecular markers, including p53, 53 ErbB2, 54 heat shock proteins, 33 and DNA sequence copy number increases, 55 among others. Although one study showed a positive correlation between p53 mutation and Pgp, 11 two other studies showed no such correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic value of Pgp in patients with osteosarcoma also should be examined in the context of other proposed molecular markers, including p53, 53 ErbB2, 54 heat shock proteins, 33 and DNA sequence copy number increases, 55 among others. Although one study showed a positive correlation between p53 mutation and Pgp, 11 two other studies showed no such correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 13 studies were excluded because they overlapped with another larger study (n ϭ 2 studies 24,25 ), they included no data on response to chemotherapy or clinical disease progression (n ϭ 6 studies 26 -31 ), they included no Pgp measurements (n ϭ 2 studies 32,33 ), or they included Ͻ 10 osteosarcomas or no osteosarcomas (n ϭ 3 studies 34 -36 ). Fourteen independent studies were entered in the meta-analysis (Table 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…One study of GSTP1 expression in samples from pediatric patients with osteosarcoma showed that GSTP1 expression might have a bearing on the outcome of treatment with chemotherapy (14). Another study by Bruheim et al (15) showed that the GSTP1 mRNA level was inversely correlated with doxorubicin growth inhibition in human osteosarcoma xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…Although the expression level of HSP27 is reportedly quite low or hardly detectable in unstimulated osteoblasts (28), we herein showed that TNF-α-stimulated IL-6 synthesis was modulated by the HSP27 expression level and/or its phosphorylation status in osteoblast-like MC3T3-E1 cells. It has been shown that osteosarcoma specimens with overexpressed HSP27 are associated with poor prognosis (51). Although rheumatoid arthritis is mainly caused by inflammation of synovial cells, our results suggest that the expression level of HSP27 in osteoblasts may correlate to the clinical symptoms or inflammatory sings of rheumatoid arthritis patients.…”
Section: Discussionmentioning
confidence: 53%